Contextualizing Disney Comics within the Arab Culture - Zitawi, Jehan (Meta, 2008)
AbstractThis paper examines the strategies adopted by Arab translators to contextualize Disney comics within the Arab culture, with particular reference to Egyptian and Gulf translators. The researcher attempts to establish the ways in which Arab translators, working under the supervision of three major publishing houses in the Arab world, intervene to adapt the source text to the target context and culture. The researcher also attempts to analyse the way Disney characters have been portrayed in the target text and examines the new dimensions added to Disney characters’ performance, actions, speech, etc. in the translated context.